Persepsi Penyakit dan Self Care Pasien Sindrom Korone Akut - Ode Irman (Pusat Riset dan Inovasi Nasional, 2026)
Acute Coronary Syndrome (ACS) remains a leading cause of death worldwide. Therefore, good self-care is essential to prevent recurrence, improve quality of life, and reduce complications. Self-care is influenced by disease perception, but its relationship in ACS patients remains understudied. The purpose of this study was to explain the relationship between illness perception and self-care in ACS patients. This was a correlational analytic study with a cross-sectional design. A sample of 42 individuals was selected according to research criteria and purposive sampling was used. The study was conducted from September to October 2025 at the Cardiology Clinic. Data on illness perception were collected using the Brief Illness Perception Questionnaire (B-IPQ). Self-care was measured using the Self-Care of Coronary Heart Disease Inventory (SC-CHDI) questionnaire. Data were analyzed using the Pearson correlation test. The results showed a relationship between illness perception and self-care in ACS patients. The direction of the relationship was positive, meaning that the more positive the illness perception score, the better the self-care score, and vice versa. The correlation strength was 0.453 (weak category). Therefore, interventions aimed at improving perceptions have been shown to improve compliance and clinical outcomes in ACS patients. For nurses, integrating these interventions into ACS management is key to improving safe care and treatment success.